Corporate Spiritual Leadership: Model Kepemimpinan Bisnis Era Milenial dalam Menciptakan Great Corporate - Abd. Rosyid; Aang Kunaifi; Qaiyim Asyari (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
The millennial era shows an increasing spirit of religiosity, especially for the younger generation. Religious identity is one of the pride of the millennial generation to create an image and gain public trust. This article aims to find a leadership model in creating a company that is not only good but also great. To obtain this model a qualitative approach is used, with in-depth interview and observation instruments in a sharia-based accommodation business, then inductively analyzed based on the relevant theory. The research findings in this article show that there is a spiritual leadership model that meets the criteria for creating a great corporate and applicable in a millennial era that tends to be religious. Great Corporate will be created through trust built by the company through spiritual activities. This article is expected to encourage further research to determine the relevance of the company's spiritual leadership model in the goods production sector as well as quantitative research to determine the correlation between SCL on business sustainability and growth.